PENGEMASAN PEMBELAJARAN TARI GANDANG DALAM BENTUK MULTIMEDIA INTERAKTIF BERBASIS KVISOFT FLIPBOOK MAKER SEBAGAI SUMBER BELAJAR BAGI SISWA SEKOLAH MENENGAH ATAS - Rina Lestari; Iskandar Muda (Universitas Negeri Medan, 2022)
Abstract-This research is a research that aims to produce Gandang dance learning products in the form of interactive multimedia using the Kvisoft Flipbook Maker program for high school level. The packaging stages used in this research are the stages of packaging according to Cracker Jack in the stage of product completion. The research method used is a mixed method, namely quantitative descriptive which is qualitatively known as it is known that the validated data is then narrated. The sample in this study was the resource person, the gandang dance and two dancers from the students of the Dance Education Study Program. Packaging is carried out in three stages. First, collect materials, process the Kvisoft Flipbook Maker, and evaluate the product in terms of language, layout, background, and suitability of the material through a validity test and then it is ready to use. This procedure can be achieved through collaboration using the Kvisoft Flipbook Maker program. The results obtained are based on the feasibility test with a score of 72 by material experts and the results of the feasibility test with a score of 74 by media experts. The percentage of eligibility for material experts is 98.6% and the percentage of media eligibility is 96%. Thus, the results of the research on the packaging of Gandang dance learning in the form of interactive multimedia based on Kvisoft Flipbook Maker for the high school level are included in the very appropriate category for use in the field. Keywords: Packaging, Gandang Dance, Interactive, Kvisoft Flipbook Maker. Abstrak - Penelitian ini merupakan penelitian yang bertujuan untuk menghasilkan produk pembelajaran tari Gandang dalam bentuk multimedia interaktif dengan menggunakan program Kvisoft Flipbook Maker untuk tingkat SMA. Tahapan pengemasan yang digunakan dalam penelitian ini adalah tahapan pengemasan menurut Cracker Jack dalam tapah penyelesaian produk. Metode penelitian yang digunakan metode campuran yaitu deskriptif kuantitatif yang dikualitatifkan sebagaimana diketahui bahwa data yang divalidasikan lalu dinarasikan. Sampel dalam penelitian ini ialah narasumber, tari gandang dan dua orang penari dari mahasiswa Prodi Pendidikan Tari. Pengemasan dilakukan dengan tiga tahapan. Pertama mengumpulkan bahan, proses pengerjaan Kvisoft Flipbook Maker, dan evaluasi produk dari segi bahasa, tata letak, background, dan kesesuaian materi melalui uji validitas dan kemudian siap digunakan. Prosedur tersebut dapat dicapai melalui kerjasama dengan menggunakan program Kvisoft Flipbook Maker. Hasil yang didapat berdasarkan uji kelayakan dengan skor 72 oleh ahli materi dan hasil uji kelayakan dengan skor 74 oleh ahli media. Persentase kelayakan ahli materi adalah 98,6% dan persentase kelayakan media 96%. Dengan demikian, hasil penelitian pengemasan pembelajaran tari Gandang berbentuk multimedia interaktif berbasis Kvisoft Flipbook Makeruntuk tingkat SMA termasuk ke dalam kategori sangat layak untuk digunakan di lapangan. Kata Kunci: Packaging, Gandang Dance, Interactive, Kvisoft Flipbook Maker.